KERAGAMAN GENETIK BEBERAPA KLON DURIAN (Durio zibethinus Murray) ASAL JAWA BARAT BERDASARKAN SIDIK RANDOM AMPLIFIED POLIMORPHIC DNA - Yulita, Kusumadewi Sri; Murnianjari, Muna (BERITA BIOLOGI, 2010)
Durian (Durio zibethinus) is one of the most popular tropical fruits in SE Asia. Indonesia has several local clones that have not yet been widely introduced to local fruit markets. This present study aimed to assess genetic diversity of 17 clones of durian from West Java based on RAPD fingerprints. Thirty RAPDs primers were initially screened and four were selected for the analysis.These four primers (OPA 13, OPD 8, OPN 6 and OPA 18) generated 63 scorable bands to which 100% of them were polymorphic.OPA-13 at 700bp was exclusively possessed by Tambleg clone and other bands were shared among the other clones. Clustering analysis was performed based on RAPD profiles using the UPGMA method. The range of genetic similarity value among genotypes was 0.15-0.73 suggesting high genetic variation among them. Results from genetic diversity analysis based on plant propagation system showed a higher genetic diversity value in occulating (87.30%) plants than that of grafting (60.32%).